Pemberdayaan Keluarga dalam Mendukung Keberhasilan Pengobatan TB Paru di Puskesmas Medan Johor - Sri Rezeki Arbaningsih (Jurnal Pengabdian Mitra Masyarakat, 2026)
Tuberculosis (TB) remains a major health challenge in Indonesia, with family support critical to treatment success (Haryanto, 2026). This study evaluated the effect of family empowerment on supporting successful pulmonary TB treatment at Medan Johor Public Health Center. A quasi-experimental non-randomized control group pretest-posttest design was used. The intervention group received a six-week empowerment program (health education, counseling, and care demonstrations); the control received standard care. Instruments included the Family Empowerment Scale and MMAS-8. Results showed significant improvements in the intervention group for adherence (p=0.001), treatment completion (90% vs 65%), self-efficacy, and self-care activity, alongside reduced stigma. Empowerment correlated positively with adherence (r=0.464, p=0.001). Family empowerment effectively improves TB outcomes and should be integrated into primary care